A study on historical development of landownership and landed aristocracy in Pakistan. (1st September 2016) - Abbas, Mazhar; Nadeem, Abdul Majeed; Hassan, Bilal; Rafique, Muhammad Zahid; Huang, Shaoan
Abstract: Landlordism is still considered an expression of power and superiority in Pakistan like many other countries in the world. This paper is aimed at: (1) to explain the very basic concept of land ownership; both in religious and social context, (2) to sketch historical pattern of land acquisition and its exploitation for exerting social control and political pressure and keeping the masses' economic down to earth. The history of Indo-Pak demonstrates the gap between original Islamic landownership principles and actual historical practice, firstly by the first Muslims of India, then by the British and most recently by contemporary Pakistan. Conversely, post independence of Pakistan, after going through various waves of military–landlords–politico–bureaucratic rule, oligarchy has reached to such a state that even the current political administration draws its chief share from landlords. The study suggests that for economic development and uplift of the pro-poor farming community, overcoming social and political injustice and getting rid of the clutches of landlordism is the dire need of the time and society.